PENGARUH PEMBERIAN BERBAGAI DOSIS PUPUK NITROGEN TERHADAP PERTUMBUHAN DAN HASIL TANAMANJAGUNG MANIS (Zea mays saccharata) - Pernitiani, Ni Putu; Made, Usman; Adrianton, Adrianton (AGROTEKBIS, 2018)
This research aims to find out the applications of nitrogen fertilizer on the growth and yield of sweet corn and to get a better dose of nitrogen fertilizers for the growth and yield of sweet corn and usefulness of this research as an information to farmers to develop and increase crop yields of sweet corn through the use of nitrogen fertilizers and can add a reference to the science of various doses of nitrogenous fertilizers in the cultivation of sweet corn. It used randomized complete block design (RCBD) with seven treatments, namely: without urea (N0), urea 50 kg ha-1 (N1), urea 100 kg ha-1 (N2), urea 150 kg ha-1 (N3), urea 200 kg ha-1 ( N4), urea 250 kg ha-1 (N5), urea 300 kg ha-1 (N6). treatment was repeated three times to obtain 21 experimental units. The research found that the nitrogen fertilizer application very significant effect on all components of observation, several dosages of nitrogen increases the growth and yield of sweet corn. Application of the fertilizer urea 250 kg ha-1 produced better yield with the lenght of the cob (31.44 cm) and weight of the cob (10.048 ton ha-1) and same result with dosage of urea 300 kg ha-1.